A review on plastic deformation induced surface/interface roughening of sheet metallic materials - Ning Nie (Elsevier, 2021)
With the increasing demand for light weight design in industries such as aerospace and automotive, sheet metallic materials with high strength and low density have been intensively manufactured and widely applied. However, plastic deformation induced surface roughening is an undesirable and a practically unavoidable phenomenon for sheet metallic materials and becomes the subject of great attention in recent years. The evolution of surface roughening plays important roles in the strain limit of the deformation and also significantly influences the product quality and application. This paper provides a comprehensive overview of both experimental and numerical modelling contributions to understand the surface roughening behaviour of sheet metallic materials during various plastic deformation and manufacturing processes. It has been found that roughening of the free surface or necking of the interface is induced by grain scale strain heterogeneity and strongly dependent on the strain the material experienced, strain state and direction, grain size and texture, lubrication, mechanical properties of materials, rolling parameters, etc. By controlling and optimising these parameters, the surface roughening can be optimised for different materials and processing techniques to suit different applications.